The Effect Of Moringa Leaf (Moringa Oleifera Lam) And Vitamin C Combination Extract In Improving Anemia Indicators Deficiency Of White Rice Iron Male Diet Low Rice Iron - Diah Hermayanti; Wahyu Setiawan; Refa Maulana Azhar; Hawin Nurdiana (Saintika Medika, 2020)
Iron deficiency anemia is still a major health problem in developing countries. Therapy with iron preparations often causes undesirable side effects. Moringa leaf extract which is rich in iron can be used as an alternative therapy in iron deficiency, and combination with vitamin C can increase the effectiveness of iron absorption in the gastrointestinal tract. determine the effect of the combination of Moringa oleifera lam. Extract and vitamin C on the indicator of iron deficiency anemia in white rats (Rattus Novergicus Strain Wistar) who were given a diet low in iron aking rice. True experimental research design using post test only control group design. The object of this study was male white rats (Rattus novergicus Strain wistar) induced by a low-iron rice diet. The study was divided into negative control group, positive control group, the treatment group with Moringa leaf extract dose of 400 mg / kg body weight, 800 mg / kg body weight, 1,600 mg / kg body weight. The treatment group was given vitamin C in a dose of 40 mg. Results and Discussion One wayAnova test, hemoglobin sig. 0,000 (p <0.05), MCV sig 0.27 (p> 0.05), MCH sig 0.16 (p> 0.05), serum iron sig. 0,000 (p <0.05), transferrin saturation sig. 0.006 (p <0.05), and TIBC sig 0.68 (p> 0.05). Pearson correlation for hemoglobin 0.746 (sig.0,000), and linear regression with R2 0.557 (sig.0,000); for serum iron 0.742 (sig.0,000) with R2 0.551 (sig.0,000). There was an increase in hemoglobin and serum iron levels in the treatment group.